Algebraic Complete Integrability of the ⁽²⁾₄ Toda Lattice - Lietap Ndi, Bruce Lionnel; Dehainsala, Djagwa; Dongho, Joseph (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
This work aims to investigate the algebraic complete integrability of the Toda lattice associated with the twisted affine Lie algebra ⁽²⁾₄. First, we prove that the generic fiber of the momentum map for this system is an affine part of an abelian surface. Second, we show that the flows of integrable vector fields on this surface are linear. Finally, using the formal Laurent solutions of the system, we provide a detailed geometric description of these abelian surfaces and the divisor at infinity.